2015
DOI: 10.4269/ajtmh.13-0558
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an HRP-2 Rapid Diagnostic Test in Nigerian Children Less Than 5 Years of Age

Abstract: Abstract. The diagnostic performance of histidine-rich protein 2 (HRP-2)-based malaria rapid diagnostic test (RDT) was evaluated in a mesoendemic area for malaria, Kaduna, Nigeria. We compared RDT results with expert microscopy results of blood samples from 295 febrile children under 5 years. Overall, 11.9% (35/295) tested positive with RDT compared with 10.5% (31/295) by microscopy: sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were 100%, 98.5%, 88.6%, and 100%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 24 publications
3
28
9
Order By: Relevance
“…J. Parasitol., 10 (3): 120-126, 2015 The sensitivity of RDT reported in this study is lower than previous reports in Nigeria (Ajumobi et al, 2015) and other parts of the world. Sensitivities of 96, 97 and 97.6% had been reported in Zambia, Zanzibar and Thailand, respectively (Hopkins et al, 2008;Msellem et al, 2009;Nicastri et al, 2009).…”
Section: Discussioncontrasting
confidence: 55%
“…J. Parasitol., 10 (3): 120-126, 2015 The sensitivity of RDT reported in this study is lower than previous reports in Nigeria (Ajumobi et al, 2015) and other parts of the world. Sensitivities of 96, 97 and 97.6% had been reported in Zambia, Zanzibar and Thailand, respectively (Hopkins et al, 2008;Msellem et al, 2009;Nicastri et al, 2009).…”
Section: Discussioncontrasting
confidence: 55%
“…The specificity of 99.6% found in this study is higher than 93%, 88%, 98.5% and 92.7%% reported by Buchachart et al (2004); Msellem et al (2009);Ajumobi et al (2015) and Osei-Yeboah et al (2016) but less than the 100% reported by Dougnon et al (2015). This means that the probability of the RDT to detect negative cases among those that are negative with smear microscopy is as high as 99.6% and therefore prevent unnecessary treatment of those who are not having the parasite but only those with the parasite.…”
Section: Discussioncontrasting
confidence: 53%
“…The sensitivity of the RDT of 94.0% reported in this study is lower than 96%, 97%, 97.6% and 100% reported by Hopkins et al, (2008); Msellem et al (2009);Nicastri et al (2009) and Ajumobi et al (2015) but higher than the 62.5% reported by Osei-Yeboah et al (2016) in studies within and outside Nigeria. This means that the probability of the RDT to detect positive cases among those that are positive with smear microscopy is as high as 94.0%.…”
Section: Discussioncontrasting
confidence: 50%
“…Studies have shown that persistent antigenemia detectable by HRP2-based RDTs occurs in 10% of patients [5]. False-negative results also occur and have more serious consequences because patients who have parasites are not detected and may be given inappropriate treatment; this phenomenon has been noted with HRP2 tests in the presence of low- and high-level parasitemia [6, 7] . Hence, the single most intractable problem with use of RDTs is trust in and compliance with RDT-negative results, particularly if the patient could have been treated to resolve the illness.…”
mentioning
confidence: 99%